Kewajiban Keterbukaan dan Prinsip Rahasia Bank di Pasar Modal - Nazarudin Nazarudin (Fakultas Hukum Universitas Islam Indonesia, 2003)
As one of the alternative for supporting the strong hold and adding the bank capital, it can be taken through public bargaining at the stock exchange. In the public bargaining, every bank must pay attention for two basic principles, namely transparency and secrecy principles. But the instrument of the act, like number 23, 1964, The act of number 14,1967,and the act of Number?, 1992 as well as the act of number 10,1998 are unadequate of protection certainty in supporting activities.